Efektifitas Terapi Rendam Air Hangat dengan Garam terhadap Skala Nyeri Arthritis Pada Lansia Di Panti Sosial Tresna Werdha Budi Luhur Kota Jambi - Mursidah Dewi; Sovia Sovia; Putri Dwi Adha (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The aging factor caused by increace of age, often accompanied by various degenerative diseases. The dominant degenerative disease in elderly patients has the potential to require long-term care. One of the dominant occurrences is Arthritis. Problems that often arise in the elderly with arthritis are pain during activity, tingling, swelling and stiffness in the joints. Arthritis management can be done pharmacologically and non-pharmacologically, one form of non-pharmacological is warm water soaking. This research is a quantitative study, using a pre-experimental design with non-equivalent (pretest and posttest) two group design, aims to determine the effect of warm water and salt therapy on the pain scale of the elderly with Arthritis. This research was conducted at PSTW Budi Luhur Jambi, the research sample was 30 respondents. The results showed a significant difference in the mean pain scale of warm water soak therapy plus salt with warm water soak therapy without salt in the elderly with Arthritis (p-value 0,000 <p α 0,05), furthermore warm water soak therapy with salt was effective given to reduce the pain scale in the elderly with arthritis. Non-pharmacological management in the form of health education can be given to the elderly related to the management of pain. Enhancing the role of nurses as care providers can be done to provide holistic services in implementing nurses' independent actions. The role of educators to provide health education about the management of Arthritis pain, the role of facilitators and motivators in facilitating the elderly and to encourage the elderly to conduct therapy, in addition warm water soak with salt is like economical therapeutic, can be done independently.  As well as the nurse can collaborate with other health teams in the institution to manage  Arthritis pain in the elderly.